Trickster “Tipsy Lady” in Folklore of Taxi Drivers - M. A. Trostina; O. Yu. Osmukhina (Научный диалог, 2022)
The characteristic features of the trickster “tipsy lady”, formed in the folklore of taxi drivers, are investigated. The authors consider the modern type of rogue character, who plays the role of a tipsy taxi passenger and is a comic asocial character that performs both destructive and creative functions. Based on the analysis of the authentic material of urban folklore (the folklore of taxi drivers), the authors of this study for the first time identified the main features that determine this type. It is shown that by introducing dis-harmony and chaos into the “foreign” environment (the sphere of “habitation” of taxi drivers), the trickster “tipsy lady” tries to assert herself in it. It is noted that the character of oral stories and tales is characterized by unwillingness and inability to change her behavior that violates generally accepted moral norms. It is argued that the trickster “tipsy lady” performs the function of a conductor between social worlds. It has been established that she demonstrates the animal nature (lust) inherent in the representatives of the “primitive world”. It has been proven that the trickster “tipsy lady” is in a state of play and, finally, combines contradictory qualities — defiant self-confidence, on the one hand, and defenselessness, on the other. In their work, the authors of the article used historical-genetic, structural-typological methods, as well as a multi-level functional analysis of the folklore text.